Female Labor Supply and Fertility. Causal Evidence for Latin America - Darío Tortarolo (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
In this paper I study the causal relationship between fertility and female labor supply using census data from 14 Latin American countries and the U.S. over the span of three decades (1980, 1990 and 2000). Parental preferences for a gender-balanced family (mixed-sex children) is exploited as a source of exogenous variation in fertility. Although OLS estimates suggest a statistically signi cant negative relationship in the 39 censuses used, instrumental variables approach fails to identify a causal e ect in most of them. The average e ect of moving from a family with two children to more than two is statistically zero for the group of compliers. Considering a pool of married women from Latin America over the span of three decades, a negative causal e ect is found. In any case, despite having a highly accurate rst-stage and indirect evidence consistent with the internal validity of the instrument, the analysis of the quality of the instrument reveals a weak explanatory power of sibling sex composition on fertility. The noisy and imprecise IV estimates for Latin America in the second-stage can be attributed to the problem of weak instruments.
Keywords: J13; J22; 330; Causality; Female Labor Supply; Fertility; Latin America